Highly Concentrated, Ultrathin Nickel Hydroxide Nanosheet Ink for Wearable Energy Storage Devices - Shi, Peipei (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.